PEMANFAATAN GADGET DALAM MEMAKSIMALKAN PELAYANAN MASYARAKAT - Nur Afni Khafsoh (The Indonesian Journal of Public Administration (IJPA), 2017)
Abstract: The use of gadgets in children has a positive and negative impact. The positive impact of using gadgets among others can help learn the child and can provide information about the broad knowledge and easy way to access it. While the negative impact is decreased socialization with others, addictive effects, resulting in decreased visual function and others. However, from all the shortcomings, it would be good impact the use of this gadget can make a breakthrough for the government in running the program. As is known, public service is one of the programs provided by the government in the development process, often the government program is not running properly due to the many inhibiting factors, such as access that is difficult for the public to get information, the mainset of the government that is still traditional to the public indifference in the government program . This has become a challenge for the government to create a breakthrough in government policy. As with using gadgets in the process of program socialization or program implementation. At the same time invite the community to participate actively in the development process, especially pembangunnan village potential to be developed. However, it is not easy to use technological advances in the implementation of government programs. The obstacles faced are infrastructure preparation and human resource capability. So that community participation in the development process can increase and society can be the subject in the nation's progress. Keywords: Gadget, Community Service, Technology Utilization Abstrak: Penggunaan gadget pada anak memiliki dampak positif dan negatif. Dampak positif dari penggunaan gadget yaitu dapat membantu belajar anak, dapat memberikan informasi tentang ilmu pengetahuan yang luas dan mudah mengaksesnya. Sedangkan dampak negatifnya yaitu menurunnya sosialisasi dengan orang lain, memberikan efek kecanduan, mengakibatkan menurunnya fungsi penglihatan dan lain-lain. Namun, dari segala kekurangan tersebut, alangkah baiknya dampak penggunaan gadget ini dapat menjadikan terobosan bagi pemerintah dalam menjalankan programnya. Seperti diketahui, pelayanan masyarakat menjadi salah satu program yang disediakan pemerintah dalam proses pembangunan, seringkali program pemerintah tidak berjalan sesuai mestinya dikarenakan banyaknya faktor penghambat, seperti akses yang sulit dimiliki masyarakat untuk mendapat informasi, mainset oknum pemerintah yang masih tradisional hingga ketidakpedulian masyarakat dalam program pemerintah. Hal ini menjadi sebuah tantangan bagi pemerintah untuk menciptakan terobosan dalam kebijakan pemerintah. Seperti dengan menggunakan gadget dalam proses sosialisasi program ataupun pelaksanaan program. Sekaligus mengajak masyarakat untuk berpartisipasi aktif dalam proses pembangunan, terutama pembangunnan desa yang potensial untuk dikembangkan. Namun, tidak mudah menggunakan kemajuan teknologi dalam pelaksanaan program pemerintah. Kendala yang dihadapi adalah persiapan infrastruktur dan kemampuan sumber daya manusia. Tentunya hal ini dapat meningkatkan partisipasi masyarakat dalam pembangunan. Kata kunci: Gadget, Pelayanan Masyarakat, Pemanfaatan Teknologi